Gestão dos recursos hídricos no Rio Grande do Norte - Juliana Felipe Farias; Rodrigo de Freitas Amorim; João Correia Saraiva Júnior (Confins)
The high demand for water resources needs more management systems efficiency and quick responses, especially in places with high variability and water shortages. In a scenario of low availability of water resources, States like Ceara, Pernambuco, Paraíba and Rio Grande do Norte must constantly seek solutions to mitigate difficulties related to the collection and distribution of water. In this context, the complexity of water management in Rio Grande do Norte requires the participation of all segments of society in an orderly and solidarity manner. The State as an articulator of grants, funding and emergency actions related to supplies and conflicts by the use of water has a structure enclosed with state agencies articulated to other sectors responsible for such actions. In this sense, this paper presents the institutional organization of the water resources management of Rio Grande do Norte, showing its various aspects. In order to conduct the research, legal instruments were consulted, specifically to the management of water resources, review of scientific articles, fieldwork and interviews with representatives of representatives that make up the water management. The results show that there is still a lack of understanding as to the functions of some participating entities in the management of water resources, especially municipalities, State agencies and users. At the same time, it is possible to observe that the actions of management in the State have been concentrated in the construction of dams, pipelines, drilling and installation of desalinator, as a way to ensure water security for multiple uses. Finally, it is clear that the actions deployed by the State, over time, have maintained the basic care of water supply to the population, yet still need to consolidate the physical infrastructure and management to be assured access to water by several users.